A new species of the Scinax cruentomma group (Anura: Hylidae) from the Ucayali River basin of Loreto, Peru - Gagliardi-Urrutia, Giussepe; Araujo-Vieira, Katyuscia; Padial, José M.; Simões, Pedro Ivo; Faivovich, Julián; Castroviejo-Fisher, Santiago (Zootaxa, 2024)
We describe a new species of the Scinax cruentomma species group, with a red streak in the iris and a weakly bilobate vocal sac. It is known from oligotrophic soils in the sedimentary basin of the Ucayali River near Jenaro Herrera (province of Requena, Peru) and Río Blanco (buffer zone of the Matses Indigenous territory and reserve). The new species can be distinguished from the other species of the S. cruentomma group by its small snout-vent length, body and iris color patterns, weakly bilobate vocal sac, myological characters, and the number of notes and pulses of the advertisement call. It is morphologically most similar to S. strussmannae, from which the advertisement call, nostril, canthus rostralis, and loreal region can distinguish it.